Achievement of Cognitive Development Aspects of Children Aged 5-6 During the Covid-19 Pandemic at Santa Sesilia Kindergarten, East Flores Regency - Engelbertus Nggalu Bali; Maria Alberta Lein; Putu Agus Indrawan (Universitas Nusa Cendana, 2023)
This study aims to describe the Achievements of Cognitive Development Aspects of Children Aged 5-6 Years before the Covid-19 Pandemic, and the Achievements of Children's Cognitive Development during the Covid-19 Pandemic, at Santa Sesilia Kindergarten, Lewokluok Village, Demon Pagong District, east Flores Regency. The method used in this study is a qualitative approach. Interview data collection techniques and documentation studies. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results showed that the achievement of aspects of children's cognitive development before the covid-19 pandemic, most of their children were in the category of developing very well and developing as expected, and the achievement of aspects of children's cognitive development during the covid-19 pandemic showed that most children were in the category of undeveloped and began to develop. The conclusion of this study is that the achievement of aspects of cognitive development of children who were in the school year during the covid-19 pandemic decreased because most of their children were in the category of undeveloped and began to develop, compared to children who were in the school year before the covid-19 pandemic, most of whose children were in the category of developing as expected and developing very well.